TINGKAT KEPADATAN Vibrio sp. DAN KELIMPAHAN PLANKTON PADA PERTUMBUHAN UDANG VANNAMEI (Litopenaeus vannamei) DI CV REJO ROYAL BANYUWANGI JAWA TIMUR - Atika Marisa Halim; Anna Fauziyah; Lusiana B. Ritonga; Moh. Zainal Arifin; Ajeng Wulandari (Jurnal Perikanan Pantura (JPP), 2023)
Rejo Royal is a company that is active in producing and developing vannamei shrimp culture that has implemented an intensive technology system. Calculation of vibrio and plankton is very necessary in vannamei shrimp farming activities, it affects in productivity. Therefore, it is necessary to calculate the density of vibrio and abundance of plankton to support the productivity of vannamei shrimp farming. The purpose of this study was to find out how to check vibrio density and plankton abundance on the productivity of vannamei shrimp culture. TBC and TVC calculations were carried out in ponds A4 and A6 using a hand counter once every 10 days. Calculation of plankton abundance using a haemocytometer is done every 5 days. The abundance of plankton in the waters is very beneficial, to suppress the development of Vibrio sp. Pond C4 in DOC 20 with an abundance of 9.0x10³ cells/ml plankton was able to suppress TVC 2.9x10³ CFU/ml. Whereas, pond C6 in DOC 20 with an abundance of plankton 6.8x10³ cells/ml was able to suppress TVC 3.8x10³ CFU/ml. The abundance of vibrio affects the productivity of shrimp, wherease the higher TVC affects the decrease in Average Daily Growth. TVC in Pond C4 at DOC 90 with an abundance 2.2x10³ CFU/ml affected decreament of ADG by 0.45 gr. Likewise, the lower the TVC affects increament of ADG. TVC in Pond C6 with abundance 2.4x10³ CFU/ml affected increament of ADG by 0.57 gr.